Bake that cake! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
You never knew that they bake cakes in Barbados? I tell you, it s almost become the national symbol of that dynamic Caribbean island. It seems that just about everybody who was at Caribbean Expo in London, England, between 27 and 29 July 2001...